Influência de informações químicas interespecíficas no comportamento de predadores intraguilda (Araneae: Lycosidae: Trochosa spp. C.L. Koch 1847) em resposta à assimetria de tamanho e ao estado alimentar - Silva, Michael Wanderlei da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2013)
The indirect detection of prey and predators by allelochemicals may have an important influence on the coexistence of wandering spiders that incur mutual intraguild predation like lycosids. However, aspects of this interaction have been studied only in a few wolf spiders’ species. The detection of allelochemicals allows evaluation between the predation risk and the benefits of prey availability, which can generate behaviors of preference and avoidance of patches in these spiders. The risk of predation between a pair of spiders often is related to the size asymmetry and feeding status, such that successful predation increases the larger and hungrier is one of the spiders in relation to another. We determined the influence of size asymmetry and feeding status on the behavior of preference or avoidance of patches, guided by mutual perception of allelochemicals in wolf spiders that can engage in symmetric intraguild predation: Trochosa sp. 1 (the smaller) and Trochosa sp. 3 (the larger). Each morphospecies was subjected to different conditions of size asymmetry between the receiver and the emitter of allelochemicals, and of feeding status of the receiver (20 replicate/treatment): smaller/hungry, smaller/satiated, larger/hungry and larger/satiated. All spiders were kept in the laboratory under a 12 h light/12 h dark photoperiod for at least seven days before being used in an assay. The collection of allelochemicals was performed confining each emitter spider in a recipient whose bottom was covered with filter paper for 48 hours. The essays consisted of allocating the spiders to arenas that had two sides with filter paper substrate, one with and another without allelochemicals, at the same proportion. For each spider, it was determined the proportion of occurrence of the receiver on the patches with allelochemicals in 42 records, one every 10 minutes, from 19 h to 02 h. All essays were performed under soft red lighting. Based on the mean proportion of the occurrences on patches with allelochemicals, Trochosa sp. 1 preferred patches with allelochemicals of Trochosa sp. 3 as smaller/hungry and larger/satiated, while Trochosa sp. 3 preferred patches with allelochemicals of Trochosa sp. 1 in almost all conditions, excluding when it was larger/satiated. For both, there was no avoidance behavior. The size asymmetry and the feeding status influenced the behavior of preference of sites by chemical stimuli in Trochosa sp. 1 but such factors had no influence on Trochosa sp. 3. Trochosa sp. 1 recognized the relative size of Trochosa sp. 3 by detection of its allelochemicals. When hungry, Trochosa sp. 1 preferred sites containing allelochemicals from larger spiders, ignoring the predation risk, which did not occur when it was satiated. We believe that the differences in behavioral responses during chemical orientation between Trochosa sp. 1 and Trochosa sp. 3 resulted from a distinct predation pressure between them, raised by the difference in their absolute size. As far as we know, this is the first record of interspecific chemotactile perception for tropical climate wolf spiders.
Keywords: Aranhas; Aranhas-lobo; Aleloquímicos